2021
DOI: 10.3390/ijerph18041967
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Drug Use Patterns during the COVID-19 Pandemic in Italy: Monitoring a Vulnerable Group by Hair Analysis

Abstract: From 22 March until 18 May 2020, a complete lockdown in Italy was ordered as a countermeasure against the COVID-19 pandemic. Social isolation measures affect some populations more than others, and people with drug and/or alcohol disorders (SUDs) are more likely to be adversely affected. This study presents, for the first time, laboratory data on the use of alcohol and drugs in a high-risk population during Italy’s first wave of the COVID-19 pandemic. Thirty subjects with SUDs were monitored for the use of illi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 30 publications
(51 reference statements)
1
33
1
6
Order By: Relevance
“…This hypothesis is in line with the findings of another Italian study, which highlighted an overall significant reduction in the use of substances during the lockdown period compared with the pre-lockdown control period and significant changes in drug/alcohol use patterns during Covid-19 confinement. 67 Our observations were confirmed by the regression model applied, which highlighted as risk factors for UPC in ER living in a psychiatric facility, being a patient in care in MHC, suffering from maladjustment disorders and not being affected by any medical disorders. On the contrary, being student, use of substance and alcohol in comorbidity, suffering from manic state, other motivations for UPC (as anorexia and other eating disturbances) and having been diagnosed with psychiatric diagnoses were protective factors for seeking help in ER during pandemic.…”
Section: Discussionsupporting
confidence: 76%
“…This hypothesis is in line with the findings of another Italian study, which highlighted an overall significant reduction in the use of substances during the lockdown period compared with the pre-lockdown control period and significant changes in drug/alcohol use patterns during Covid-19 confinement. 67 Our observations were confirmed by the regression model applied, which highlighted as risk factors for UPC in ER living in a psychiatric facility, being a patient in care in MHC, suffering from maladjustment disorders and not being affected by any medical disorders. On the contrary, being student, use of substance and alcohol in comorbidity, suffering from manic state, other motivations for UPC (as anorexia and other eating disturbances) and having been diagnosed with psychiatric diagnoses were protective factors for seeking help in ER during pandemic.…”
Section: Discussionsupporting
confidence: 76%
“…However, correlations of prescription drugs and ‘other’ drugs with heroin, cannabis, and alcohol were significant at wave 2, but not at wave 1, suggesting that some transfers from one of these drugs to another might have cancelled the correlations found at wave 1. In a study among thirty subjects with substance use disorder (not receiving OAT), hair analysis showed that samples positive for heroin, cocaine, MDMA and cannabis fell considerably during the lockdown while the consumption of benzodiazepines and alcohol followed the opposite trend [ 28 ]. Some were concerned that shortages in heroin supply would lead to the consumption of other substances, such as fentanyl and its derivatives, or resold pharmaceutical products, such as benzodiazepines and buprenorphine [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, isolation induces a reduction in PFC dendritic dopamine D2 receptors which can be rescued by CB1 stimulation (76). Where cannabis was more available, an increase of its use during lockdown measures was reported, perhaps highlighting an intuitive understanding by consumers for the need to increase the eCB tone (77)(78)(79)(80)(81). The increased cannabis use was self-administered, yet not associated with an increase in DSM-5-CCSM total, depression, anxiety, and sleep problem scores in these Countries (78).…”
Section: Phytoceutic Interventionsmentioning
confidence: 99%